Elaboración de biopelícula a partir de la semilla de aguacate variedad Lorena (2023)
The present work describes the development of a biofilm starting from the starch of the avocado seed. To choose the starch extraction methods, a PUGH matrix was made in order to select the most suitable one or more, choosing the wet and dry method, with these the yield, % moisture, % ash is calculated and the test of Lugol as tests to characterize starch, the wet method was finally selected despite the differences in performance.